Data and network communications - Miller, Michael A. (Delmar Thompson Learning, 2000)
This text provides a solid, thorough overview of the field of data communications and networking. Beginning with the basics of a two-point communications link, it includes hardware and protocol standards at all levels of the open systems (OSI) communications model. Each chapter features an explanation of acronyms, making it easy for students to learn the terms unique to this field. Complete network coverage begins with LANs like Ethernet and token ring. It goes on to include ATM, FDDI, TCP/IP, frame relay, satellite and wireless communications, Internet structure and use, and network security. This text is well suited for students at two-year associate and four-year bachelor's institutions with electronic engineering technology and electronic technician curriculums.